Dokumenty i sud'by . Dokumenty i sud'by . Documents and Destinies . Документы и судьбы - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
This program was broadcast by Ostankino television (Moscow) in the Russian Federation and recorded by the moniotring group at the Research Institute of Radio Free Europe/Radio Liberty in Munich as part of their effort to track and analyze the official media of the countires of the former Soviet Union. Передача Российской государственной телевизионной и радиовещательной компании (РГТРК) "Останкино" (Москва, Российская Федерация) была записана группой мониторинга Исследовательского Института радиостанции Свободная Европа/Свобода (Мюнхен) как часть проекта по анализу официальных средств информации стран бывшего Советского Союза. Program on the Order of the Minister of Internal Affairs of the USSR from April 4, 1953, "On prohibition of applying any coercion and physical action to the arrested," signed by Lavrentii Beria. Contributors: Mironenko, Sergei (Anchor) Передача рассказывает о приказе Министра Внутренних дел СССР от 4 апреля 1953 года "О запрещении применения к арестованным каких-либо мер принуждения и физического воздействия", подписанном Лаврентием Берией. Создатели: Мироненко, Сергей (Ведущий/Ведущая)